Performance indices for feedforward control. (February 2015) - Guzmán, J.L.; Hägglund, T.; Veronesi, M.; Visioli, A.
Abstract : Highlights: We propose a new performance index to evaluate the contribution of feedforward control. Metrics to estimate Integral Absolute Error are provided for feedback and feedforward. The resulting index is derived for the two most common feedforward schemes. Abstract: In this paper, a performance benchmark for the assessment of two feedforward control architectures for the load disturbance compensation problem is proposed. In particular, two indices are devised so that the advantage of using a feedforward compensator with respect to the use of a feedback controller only is quantified. Furthermore, these metrics will help to make quantitative comparisons among different feedforward control schemes and tuning rules. Analysis and simulation results are given to demonstrate the effectiveness of the proposed approach.